Monkeypox: A Contemporary Review for Healthcare Professionals - Titanji, Boghuma K; Tegomoh, Bryan; Nematollahi, Saman; Konomos, Michael; Kulkarni, Prathit A (Open forum infectious diseases, 2022)
Abstract The ongoing 2022 multicountry outbreak of monkeypox is the largest in history to occur outside of Africa. Monkeypox is an emerging zoonotic disease that for decades has been viewed as an infectious disease with significant epidemic potential because of the increasing occurrence of human outbreaks in recent years. As public health entities work to contain the current outbreak, healthcare professionals globally are aiming to become familiar with the various clinical presentations and management of this infection. We present in this review an updated overview of monkeypox for healthcare professionals in the context of the ongoing outbreaks around the world. Monkeypox is an emerging zoonosis of global health concern. Healthcare professionals worldwide should become familiar with the clinical presentations and management of this viral infection in light of contemporary outbreaks.